АНАЛІЗ ТРАКТУВАННЯ ПОНЯТТЯ “МОРАЛЬНІ ЦІННОСТІ” В НАУКОВІЙ ЛІТЕРАТУРІ (Педагогіка вищої та середньої школи, 2022)
The article is devoted to the analysis of the various approaches to treatment of concepts of "value" and "moral values" in the scientific literature, that has allowed the author to make a line of generalizations on the given problem.